Gotcha! - Jorgensen, Gail. (New York : Scholastic Press, 1997)
When Bertha Bear's birthday party is interrupted by a pesky fly, she races off in pursuit of it and disturbs a number of animals along the way.
Adult 320
Keywords: Birthdays -- Juvenile fiction; Bears -- Fiction; Flies -- Fiction; Birthdays -- Fiction; Animals -- Fiction